Beef Consumption Demand of Consumer in 3 Southern Border Provinces - Limcharoen, Somnuek; Jun-iad, Jamnong (Princess of Naradhiwas University Journal, 2019)
The objectives of this study were 1) Consumer behavior for meat cattle 2) Attitude and behavior of meat cattle 3) Factors marketing mix of beef cattle 4) Need extension for process beef cattle of consumer and 5) Problems and Suggestion for meat cattle consumed by Consumers in 3 southern border provinces, 400 samples (Simple Random Sampling: SRS) were selected from these consumers of meat cattle by using simple random sampling methodology. The data were collected by using interview forms. Data were analyzed using frequency, percentage, minimum and maximum, value mean, and standard deviation, and multiple regression analysis. The results revealed most consumers meet cattle (Male) 56.0 %, Average age is 38.60 years. Islam 90 %, Consumers eat meet cattle because it tastes good 88.0 %. Eating cook yourself by 90.0 %. Head of the family (Male) decided to buy 42.0.Meet cattle buy for fresh market 92.0%. Buy for live cattle for religious ceremony 96.0 %. Attitude and behavior of meat cattle. high level. meet cattle can be cooked almost all. Great taste fresh and clean. Meet Cattle for great taste. Meet cattle is expensive. and Beet cattie of nutritious. Factors marketing mix of beef cattle high level. Factor of product/packaging. Price. distribution channel. and middle level for promotion. The hypothesis is tested utilizing multiple regression analysis method. The result of this research factor of the product/packaging and factor attitude and behavior of meat cattle effect on the positive result. And factor of the price. factor of the distribution channel factor of the Promotion and factor attitude and Behavior of meat cattle effect on the positive result. Need extension for process meet cattle of Consumer. Middle level for extension for knowledge. and extension of met cattle processing. And high level needs extension are supported. They were high level in the problem of high price. Great taste fresh and clean. Therefore, Relevant government agencies should support farmers. Produce meat cattle of required by the market and consumers.